The Effect Of Ketapang Leaves Extracts (Terminalia Catappa) In Inhibiting The Growth Of Bacteria Edwarsiella Tarda On In Vitro Test - Maryani Maryani; Shinta Sylvia Monalisa; Rekonsili Soritua Panjaitan (JURNAL PERIKANAN DAN KELAUTAN, 2020)
This study was conducted to find out the effectiveness of ketapang (Terminalia catappa) leaves extracts, as well as determine the best dose of the extract of ketapang leaves (Terminalia catappa) in inhibiting the growth of bacteria Edwardsiella tarda. Method that used in this research is descriptive method with 6 treatments and 3 replications, such as giving the extracts of ketapang leaves as much 3 g/60 ml, giving the extracts of ketapang leaves as much 4.5 g/60 ml, giving the extracts of ketapang leaves as much 6 g/60 ml, giving the extracts of ketapang leaves as much 7.5 g/60 ml, giving the chloramphenicol 500 mg as a positive control and giving the aquades as a negative control. This research was conducted at the Testing Laboratory of Fish Quarantine Station, Quality Control and Safety of Fishery Class I Palangka Raya for 3 months from January to March 2017. The result of this research is the inhibition of a test contained in the extract of ketapang leaves (Terminalia catappa) at the dose of 3 g/60 ml; 4.5 g/60 ml; 6 g/60 ml and 7.5 g/60 ml classified in the strong category (10-20 mm) in inhibiting bacteria Edwardsiella tarda. Extract of ketapang leaves (Terminalia catappa) at a dose of 6 g/60 ml more effective as bacteriostatic be based on the average of bigger diameter inhibition zone, it is 15.33 mm than the treatment of others ketapang leaves extracts (Terminalia catappa). In the test MIC (Minimum Inhibitory Concentration) treatment with a dose of 3 g/60 ml was able to inhibit bacterial growth Edwardsiella tarda. The disc test and MIC (Minimum Inhibitory Concentration) test showed that the extracts of ketapang leaves (Terminalia catappa) effective as bacteriostatic, it has seen from its ability to inhibit the growth of bacteria Edwardsiella tarda.